Ratio Legis Kewenangan Diskresi Ankum dan Papera dalam Penyelesaian Perkara Pidana Militer: Antara Kepentingan Operasional dan Kepastian Hukum - Hendry Maulana (Jurnal Ragam Pengabdian, 2026)
The existence of discretionary authority vested in the Military Commander with Authority to Punish (Ankum) and the Military Officer in Charge of Case Submission (Papera) within Indonesia's military criminal justice system is frequently narrated reductively as an anomaly of the rule of law and an instrument for perpetuating institutional impunity. This study rejects such oversimplified dichotomy by proposing a comprehensive and multi-dimensional theoretical justification that integrates the philosophy of legal sociology with the operational reality of national defense. Through a doctrinal legal research approach collaboratively employing socio-legal analytical instruments, this study demonstrates that the discretion exercised by Ankum and Papera constitutes a form of functional and inevitable jurisdictional specialization, rather than an instrument of impunity. By way of Roscoe Pound's sociological jurisprudence framework, national defense interests are identified as a social interest in general security occupying the highest hierarchical position, thereby demanding legal evaluation grounded in operational reality (law in action). Employing Niklas Luhmann's theory of functional differentiation, the military institution is analyzed as an autopoietic social subsystem operating under a binary code of operational/non-operational distinction, fundamentally divergent from the legal/illegal code characterizing the civil law subsystem. This study recommends that the military legislative reform agenda be directed toward reinforcing internal accountability mechanisms and clarifying the normative boundaries of discretionary authority, rather than its wholesale elimination.